PERBANDINGAN STRATEGI PEMASARAN SKINCARE ANTARA MS GLOW DAN WARDAH DI KOTA PONTIANAK - Dhea Crista Sheva Anandauri; Dina Octaviani; Arweni Ibrahim (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2025)
This study aims to analyze the differences in skincare marketing strategies between MS Glow and Wardah in Pontianak City. The method used is associative quantitative with purposive sampling technique on 118 respondents, consisting of 59 MS Glow users and 59 Wardah users. Data were analyzed using the Cochran Q Test via SPSS 23. The results of the study showed significant differences in the marketing strategies of the two brands, indicated by the calculated Q value of 43.27 with a significance of 0.000 < 0.05. The average score of Wardah (19.61) is higher than MS Glow (18.86), which confirms that the effectiveness of a marketing strategy is not only determined by the intensity of promotion, but also the suitability of the approach to consumer preferences. These findings are expected to be a reference for local skincare brands in developing more targeted marketing strategies and being able to compete in an increasingly competitive market